Critical Discourse Analysis as a Review Methodology: An Empirical Example - Salam, A. F. (2015)
Research disciplines and subdisciplines are steeped in epistemological beliefs and theoretical assumptions that guide and constrain research. These beliefs and assumptions both enable scientific inquiry and limit scientific progress. Theory and review papers tend to be a means for reproducing ideological assumptions. However, review papers can also challenge ideological assumptions by critically assessing taken-for-granted assumptions. Critical review methods are underdeveloped in the management disciplines. The information systems (IS) discipline must do more to improve the critical examination of its scientific discourse. In this paper, we present a method with guiding principles and steps for systematically conducting critical reviews of IS literature based on Habermasian strains of critical discourse analysis. We provide an empirical example of the method. The empirical example offers a critical review of behavioral information security research with a focus on employees’ security behaviors